How Different Are Immigrants? : A Cross-Country and Cross-Survey Analysis of Educational Achievement - Sylke Viola Schnepf (Institute for the Study of Labor (IZA), 2004)
This paper examines differences in educational achievement between immigrants and natives in ten countries with a high population of immigrant pupils: Australia, Canada, France, Germany, the Netherlands, New Zealand, Sweden, Switzerland, the UK and the USA. The first step of the analysis shows how far countries differ regarding immigrants? educational disadvantage. In a second step, the paper compares immigrants? characteristics across countries focusing predominantly on socioeconomic status, language proficiency, immigrants? time spent in the host country and patterns of school segregation. Using a regression framework the last step of the analysis investigates how far these determinants of educational achievement can explain immigrants? educational disadvantage in the countries examined. The paper evaluates whether results found are robust across different sources of achievement data: the Trends in International Maths and Science Study (TIMSS), the Programme of International Student Assessment (PISA) and the Programme of International Reading Literacy Study (PIRLS).
Keywords: O15; J15; I21; 330; education; immigration; PISA; TIMSS; PIRLS; Migranten; Bildungsniveau; Bildungschancen; Schätzung; Australien; Kanada; Frankreich; Deutschland; Niederlande; Neuseeland; Schweden; Schweiz; Vereinigte Staaten; Grossbritannien